2019
DOI: 10.25165/j.ijabe.20191201.3015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic ultra-high pressure homogenization on the structure and functional properties of casein

Abstract: Dynamic ultra-high pressure homogenization (UHPH) is a novel high-pressure processing technique. In this study, the effects of dynamic UHPH on the structure and functional properties of casein were systematically investigated. It was found that the functional properties of casein changed with dynamic UHPH treatment, and the treatment at 150 MPa could significantly improve casein aqueous solubility, foaming and emulsifying properties. These functional improvements could be attributed to its structural changes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…However, MEF applications affected and rearranged the CAS for particle size and air/water interfacial activity more than ultrasound treatment (de Figueiredo Furtado, Mantovani, Consoli, Hubinger, & da Cunha, 2017). Wang et al (2019) confirmed the relation of smaller particle size whey protein for having better air/water interfacial activity after highpressure treatment. Beside these static environment results, more detailed information about the non-thermal effect of MEF on proteins surface activity could be observed with a dynamic study (Benjamins, De Feijter, Evans, Graham, & Phillips, 1975).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 72%
See 2 more Smart Citations
“…However, MEF applications affected and rearranged the CAS for particle size and air/water interfacial activity more than ultrasound treatment (de Figueiredo Furtado, Mantovani, Consoli, Hubinger, & da Cunha, 2017). Wang et al (2019) confirmed the relation of smaller particle size whey protein for having better air/water interfacial activity after highpressure treatment. Beside these static environment results, more detailed information about the non-thermal effect of MEF on proteins surface activity could be observed with a dynamic study (Benjamins, De Feijter, Evans, Graham, & Phillips, 1975).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 72%
“…150 V exposure for 5 sec (V5) significantly produced the smallest particle solution with the highest intensity. In their study, Wang et al (2019) emphasized that casein samples had smaller particles due to the shear force of ultra-high pressure application however, reaggregation occurred when increased the applied pressure. Similarly, prolonging the application after 5 sec, the most intense aggregations were obtained within the next 15 sec (V20) throughout the solution.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the further increase of homogeneous pressure, the change of temperature tends to be gentle, and the difference between 200 and 250 MPa was not significant, which indicated that the increase of pressure could lead to higher material temperature within a certain range, which revealed that the higher pressure could not result in the greater change of temperature. It was also reported that the temperature of casein solution could be controlled below 55 °C by dynamic UHPH treatment (\ 250 MPa) (Wang et al 2019). Compared with the traditional thermal processing, it is more moderate and energy-saving (Dissanayake et al…”
Section: Resultsmentioning
confidence: 99%
“…However, these modifications depend on the matrices and pressure parameters applied, such as pressure level, process temperature and the number of passes. These particular modifications of protein structure and interactions induced by UHPH were studied to improve the techno-functional properties of proteins [ 21 , 22 ], such as emulsifying [ 23 , 24 , 25 , 26 ] and foaming [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%